Exploring the geographies of academic social network sites from a socio-technical perspective: An investigation of scientific literature in Spanish - Raffaghelli, Juliana Elisa; Manca, Stefania (Proceedings of the International Conference on Networked Learning, 2018)
Academic social network sites (ASNS) like ResearchGate and Academia.edu can be analysed as techno-cultural systems through which researchers perform a number of tasks and roles that can be collectively defined as digital scholarship. This study sets out to map empirical Spanish-language research studies on the use of ResearchGate and Academia.edu among scholarly communities. The aim is to verify possible research gaps regarding shared scholarly knowledge and networked learning supported by ASNS. The study is based on a theoretical framework which treats ASNS as networked socio-technical systems that encompass systemic dimensions and individual usage as strictly intertwined elements influencing each other. This occurs at three levels: 1) the socio-economic level, which includes components like ownership, governance, and business model; 2) the techno-cultural level, which includes components associated to technology, user/usage, and content; and 3) the networked-scholar level, which includes components related to networking, knowledge sharing and identity. The research reported here is an extension of a previous study of English-language scientific literature which was carried out with the same methods. The corpus of the study was collected from a search of leading databases of international scientific literature (Web of Science, Scopus and a number of Ibero-American scientific databases). The search yielded 12 papers, which were selected according to a set of criteria and analysed in terms of components of the aforementioned three-level framework. The results show that ResearchGate is attracting greater attention, with a particularly high proportion of studies dedicated to social science areas like library and information sciences and communication science. Analysis at the networked scholar level, encompassing forms through which scholars build their identities and reputation in social spaces, revealed that this was underused. The results highlight a need for more specific studies on open and distributed knowledge exchange generated in ASNS from a networked learning perspective, including both individual and collective scholarly practices. Moreover, increased use of qualitative methods could contribute to shed light on new practices among scholars for building reputation and professional identity.